Mediterranean Diet and Fatigue among Community-Dwelling Postmenopausal Women. Issue 1 (2nd January 2022) - Su, Yan; Cochrane, Barbara B.; Reding, Kerryn; Herting, Jerald R.; Tinker, Lesley F.; Zaslavsky, Oleg
Abstract: We investigated cross-sectional relationships between the Mediterranean diet and overall fatigue, energy, and weariness scores among 4, 563 women aged 65+ from the Women's Health Initiative study. We also used the Isocaloric Substitution approach to explore whether the substitution of fish for red and processed meat, whole for non-whole grains, and whole fruit for fruit juice relate to RAND-36 measured overall fatigue and its subdomains. The alternate Mediterranean Diet (aMED) Index quintiles (Q1–Q5) and selected Mediterranean foods available on a Food Frequency Questionnaire were exposure measures. Results showed aMED Q5 was associated with 2.99 (95% CI: 0.88, 5.11), 4.01 (95% CI: 1.51, 6.53), and 2.47 (95% CI: 0.24, 4.70) point improvements in fatigue, energy, and weariness scores, respectively, compared with aMED Q1. Substituting fish for red and processed meat and whole for non-whole grains was associated with more favorable fatigue scores, whereas substituting whole fruit for juice was not.